Pengaruh Kompetensi, Pengembangan Karir, Komitmen Organisasi dan Kepuasan Kerja terhadap Kinerja Karyawan Perbankan - Yusuf Yusuf (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study aims to analyze the influence of competence, career development, organizational commitment and job satisfaction on the performance of banking employees in South Konawe Regency. This research was conducted by survey method to 91 Bank employees in South Konawe district. The data analysis used was descriptive statistical analysis and inferential statistical analysis using PLS SEM analysis. The results of the study show that the competence, career development, organizational commitment and job satisfaction of banking employees in South Konawe Regency have a positive and significant effect both partially and simultaneously on employee performance.